Design and fabrication of nanofibrous thin film composite membranes by electrospinning for osmotically driven membrane processes - Tian, Miao (2015)
Nowadays, high water demands due to fast global population growth and rapid economic development call for new technologies to provide clean water with less energy consumption. The serious environmental pollution caused by fossil fuel usage also require us to develop environmentally friendly technologies to harvest energy. As an emerging technology, osmotically driven membrane processes (ODMPs) including forward osmosis (FO) and pressure retarded osmosis (PRO) processes, are considered to be attractive technologies to treat waste water, recycle used water and harvest energy from salinity-gradients. However, FO and PRO technologies are still in the development stage. Developing osmotic membranes with both high water permeation and excellent ion rejection is a challenging task. The desired osmotic membrane may be a thin film composite (TFC) membrane consisting of an ultrathin polyamide layer with high water permeability and low solute permeability, and a highly porous support layer for low internal concentration polarization (ICP), which is one of the obstacles to improving FO/PRO membrane performance. In addition, high mechanical properties are essential for the membrane to withstand high hydraulic pressures in PRO processes. Fortunately, electrospun nanofibrous membranes have great potential to fulfil all the requirements of an ideal membrane support layer due to their open and porous structural features and ease with which nanomaterials can be incorporated to increase the mechanical properties of the nanofibers. Additionally, interfacial polymerization can be carried out on electrospun nanofibrous membrane surfaces to obtain an ultrathin polyamide selective layer. After incorporating nanomaterials in either the polyamide selective layer or the support layer, thin film nanocomposite (TFN) membranes may have great potential to exhibit excellent performance in ODMPs.